Medical psychiatry : theory and practice - TrevinÌƒo, Enrique S. Garza (World Scientific, 1989)
The book offers balanced coverage of subjects that receive scant attention in other introductory textbooks, including the limitations of the DSM-IV categorical approach to psychiatric diagnosis, controversies surrounding the dissociative disorders and "recovered memories," and the prescription of stimulant medications to children with suspected attention-deficit hyperactivity disorder. Later chapters provide practical guidelines for estimating a patient's risk of suicide and violence and for assessing competence to consent to medical or psychiatric treatment. In eschewing a dry recitation of clinical syndromes for an engaging discussion aimed at teaching the reader how to "think psychiatrically," the book will appeal to medical students, psychiatric residents, mental health clinicians, and primary care physicians.